AKSESSIBILITAS MASYARAKAT TERHADAP KELEMBAGAAN PEMBIAYAAN PERTANIAN DI PEDESAAN - LESTARI HASTUTI, ENDANG; -, SUPADI (SOCA: Jurnal Sosial Ekonomi Pertanian, 2012)
Community’s Accessibility on Agricultural Financing Institutions in Rural Areas. Although the government has made some policies on channeling credit for rural communities, however, agribusiness agent’s accessibility on formal financing institutions was still relatively low, moreover to those in capable of. Research results in villages of West Java and West Nusa Tenggara showed that community’s perception of the accessibility found it was difficult to be accessed to the formal financing institutions. This was due to a condition that the borrower should provide collateral of land certificate. In fact, most villagers do not have one because of expensive certificate land arrangement was relatively costly. Community’s accessibility on non-formal financing institutions was higher due to faster and simpler procedures. Therefore, an accurate and simple modification of the financing institution is required. In addition, a government policy on land certification is also badly needed.
Keywords: Accessibility, Institution, Rural Community, Rural Credit